A Strategy for Effective Tuberculosis Contact Tracing in Botswana (International Journal of Nursing Education, 2019)
Botswana has witnessed the highest TB rates in the southern African countries, ranking the fourth after South Africa, Swaziland, and Zimbabwe. In 2012, the TB rate was, on average, 531/100 000 population. About 2 380 contacts out of a possible 8 110 (amounting to 29.30%) were traced nationally (Botswana 2011:8), indicating a potential gap of 5 730, which was yet to be traced in 2011. The TBCT strategies might be inadequate leading to absence of screening and treating TB contacts and reducing PTB related deaths. The purpose of this study was to describe utilisation of current TBCT and develop a strategy for a more effective TBCT in Botswana. Data were collected through a quantitative cross-sectional research design. The study further described the association between TBCT strategies and practices and determined the gaps, challenges, and needs in the TBCT. Results revealed under-tracing of contacts in the number of registered and enumerated TB contacts. The results further established the risk of mixing TB contacts and general patients. The differences in the perceptions and knowledge of the cause of TB, as well as poor utilisation of the current programmes by the PTB patients, denotes the need for aggressive awareness-raising and health promotion strategies. The results were used to develop an alternative plan, the IC-TBCT, which has the potential to trace all TB contacts. The approach encourages participation, active accountability and involvement of the beneficiaries in all efforts aiming at early contact identification and reducing the incidence of PTB.